PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DAN ORANG TUA DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SISWA KELAS XI MIPA PADA MASA PANDEMI COVID-19 DI SMA NEGERI 4 MALANG - Alfi Umy Nurchamidah; Dian Mohammad Hakim; Eko Setiawan (VICRATINA, 2022)
During the Covid-19 pandemi, the learning system was carried out online. This is none other than to break the chain of spread of the virus. Online learning provides many problems for both teachers and students. One of them is the decline in student learning discipline. The focuses studied include: (1) Student discipline during the Covid-19 pandemi, (2) The role of PAI teacher and parents, (3), Implications of the role of PAI teachers and parents in improving learning discipline. To achieve this goal, the researches uses a qualitative descriptive approach with the type of case study research. Data collection was carried out by interview, observation, and documentation techniques. The results of this study show that: (1) Student learning discipline during the Covid-19 pandemi has decreased. (2) The role of PAI teachers and parents in educators, mentors, role models, and motivators. (3) The implication of the role of PAI teachers and parents in improving learning discipline is that students are able to manage time, the student learning process is monitored, learning objectives are achieved, and the increase in learning discipline and students learning outcomes.